Answer:
![\Huge\boxed{\mathsf{\Rightarrow X=-6}}}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rhsufthmjpk205lnu0ol5225t9o97p0drq.png)
Explanation:
Isolate x on one side of the equation.
2(-2x-4) ← (Expand by using with distributive property.)
DISTRIBUTIVE PROPERTY
⇒ A(B+C)=AB+AC
⇒ A(B-C)=AB-AC
A=2
B=(-2x)
C=4
2(-2x)-2*4
-2*2x-2*4
-2*2x-2*4 (Solve.)
-2*2-2*4=-4x-8
Rewrite the equation problem.
10-x=-4x-8
10-x-10=-4x-8-10 (Subtract 10 from both sides.)
Solve.
-x=-4x-18
-x+4x=-4x-18+4x (Then, add 4x from both sides.)
3x=-18 (Solve.)
3x/3=-18/3 (Divide by 3 from both sides.)
-18/3 (Solve & Simplify.)
-18/3=-6
X=-6
![\Large\boxed{\mathsf{X=-6}}}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6ju0mwuz6vygsfr4zujlqhiuvs5u75cwvz.png)
Therefore, the correct answer is x=-6.